E-st@r-I experience: Valuable knowledge for improving the e-st@r-II design. (April 2016) - Corpino, S.; Obiols-Rabasa, G.; Mozzillo, R.; Nichele, F.
Abstract: Many universities all over the world have now established hands-on education programs based on CubeSats. These small and cheap platforms are becoming more and more attractive also for other-than-educational missions, such as technology demonstration, science applications, and Earth observation. This new paradigm requires the development of adequate technology to increase CubeSat performance and mission reliability, because educationally-driven missions have often failed. In 2013 the ESA Education Office launched the Fly Your Satellite! Programme which aims at increasing CubeSat mission reliability through several actions: to improve design implementation, to define best practices for conducting the verification process, and to make the CubeSat community aware of the importance of verification. Within this framework, the CubeSat team at Politecnico di Torino developed the e-st@r-II CubeSat as follow-on of the e-st@r-I satellite, launched in 2012 on the VEGA Maiden Flight. E-st@r-I and e-st@r-II are both 1U satellites with educational and technology demonstration objectives: to give hands-on experience to university students and to test an active attitude determination and control system based on inertial and magnetic measurements with magnetic actuation. This paper describes the know-how gained thanks to the e-st@r-I mission, and how this heritage has been translated into the improvement of the new CubeSat in several areas and lifecycle phases. The CubeSat design has been reviewed to reduce the complexity of the assembly procedure and to deal with possible failures of the on-board computer, for example re-coding the software in the communications subsystem. New procedures have been designed and assessed for the verification campaign accordingly to ECSS rules and with the support of ESA specialists. Different operative modes have been implemented to handle some anomalies observed during the operations of the first satellite. A new version of the on-board software is one of the main modifications. In particular, the activation sequence of the satellite has been modified to have a stepwise switch-on of the satellite. In conclusion, the e-st@r-I experience has provided valuable lessons during its development, verification and on-orbit operations. This know-how has become crucial for the development of the e-st@r-II CubeSat as illustrated in this article. Highlights: CubeSat mission reliability can be increased by improving the development process. We leveraged the experience gained with e-st@r-I CubeSat to increase our know-how. E-st@r-II fixes bugs and issues discovered through the analysis of e-st@r-I mission. Modifications are applied at design, development and operations lifecycle stages. Main changes in the educational, management and technical domains are described.